PENGARUH TINGGI DAN JARAK WAKTU PEMOTONGAN RUMPUT GAJAH DWARF (pannisetum purpureum cv. Mott) TERHADAP PERTUMBUHAN VEGETATIF DAN PRODUKSI BAHAN KERING - ., Santia; Anis, Selvie D.; Kaunang, Charles L (ZOOTEC, 2017)
EFFECT OF HIGH AND DISTANCE OF CUTTING TIME OF DWARF ELEPHANT GRASS (pannisetum purpureum cv. Mott) ON VEGETATIVE GROWTH AND DRY MATERIAL PRODUCTION. This research aims to identify and obtain data about the effect of height and distance of cutting time on vegetative growth and dry material production of dwarf elephant grass (pannisetum purpureum cv. Mott). The treatments were applied into factorial design on the base of Group Random Design (GRD) which consists of two factors and three replications. Factor A were cutting height, a1 = 0 cm above the ground, a2= 5 cm above the ground, a3= 10 cm above the ground, a4= 15 cm above the ground. Factor B age of cutting, b1 = 20 days, and b2 = 30 days. The measured variables were including the number of tillers, ratio of leaf/stem and dry material production. Result of analysis of variance (ANOVA) showed that the number of tillers and dry ingredient of grass were affected very significantly (P < 0,01) by the interaction of high of cutting and the age of plant. However, the age of plant was giving a significantly different effect (P < 0,05) on the leaf/steam ratio. While the interaction high of cutting and age of plant did not significantly affect (P > 0,05) the leaf/steam ratio. Based on the research, it can be concluded that I order to ensure the continued production of P.purpureum cv.Mott measured in the number of tillers and dry ingredient, it should be cut at the age of 20 and 30 days with a cutting height of 15 cm above ground level. The highest value of leaf/steam ratio was obtained at the cutting age of 20 days.Keywords : P. purpureum cv. Mott, high and age of cutting, growth, dry material production